2016
DOI: 10.1051/shsconf/20162601105
|View full text |Cite
|
Sign up to set email alerts
|

The relative age effect on anthropometric characteristics and motor performances in Turkish children aged between 8 and 12 years

Abstract: Abstract. This study was carried out to investigate the effect of relative age on anthropometric properties and motor performance in Turkish children (girls n=423, boys n=601). Anthropometric measurement sites and techniques have been set out by the ISAK (International Society for the Advancement of Kinanthropometry). A group of tests involved in Eurofit Test Battery and other standard tests were used. For each age, the data of those who were born within the first three months and the last three months of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a result of study, there were statistically significant differences in participants' flexibility parameters. When different studies were examined, Haslofça et al (2016), examined the effect of relative age on anthropometric and motoric properties in children between 8-12 age they reported that relative age had an effect on flexibility parameter in children at 12 age and in our study relative age was not seen to have an effect on flexibility parameter in children at 9 age. Malija et al (2004), explained that neuromuscular maturation had significant effects on performance in childhood period and the difference in flexibility parameter occurs as one grows older.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As a result of study, there were statistically significant differences in participants' flexibility parameters. When different studies were examined, Haslofça et al (2016), examined the effect of relative age on anthropometric and motoric properties in children between 8-12 age they reported that relative age had an effect on flexibility parameter in children at 12 age and in our study relative age was not seen to have an effect on flexibility parameter in children at 9 age. Malija et al (2004), explained that neuromuscular maturation had significant effects on performance in childhood period and the difference in flexibility parameter occurs as one grows older.…”
Section: Discussionmentioning
confidence: 55%
“…When different studies were examined in this field, Gil et al (2007) studied anthropometric and physiological factors according to months of birth of 14 to 17 age soccer players and It was determined that 15-16-17 age soccer players were seen to have higher scores in vertical jump tests than 14 age soccer players. In a different study, Haslofça et al (2016) studied the effects of relative age on anthropometric and motoric properties between 8 and 12 age children. They determined significant differences in performance of 11 age children.…”
Section: Discussionmentioning
confidence: 99%